The Influence of Product Quality, Service Quality, Consumer Trust and Consumer Satisfaction on Consumer Loyalty - Gunawan, Richo; Prasetyoning Tyas, Ari Anggarani Winadi (PT Inovasi Pratama Internasional, 2026)
This study investigates the effects of product quality, service quality, and consumer trust on consumer loyalty to Mills Sport products, both directly and indirectly through consumer satisfaction. The research is motivated by unstable loyalty among Mills Sport consumers in West Jakarta, despite repeated purchases, which raises questions about which drivers are most critical for sustaining long‑term relationships. A quantitative survey was conducted using purposive sampling of 155 Mills Sport consumers who had purchased Mills Sport products at least twice and were at least 18 years old. Data were collected via a structured Likert‑scale questionnaire and analysed using Partial Least Squares Structural Equation Modeling (PLS‑SEM). The findings show that product quality does not significantly affect consumer satisfaction or consumer loyalty, either directly or through satisfaction. In contrast, service quality and consumer trust have significant positive effects on both satisfaction and loyalty, and consumer satisfaction significantly reinforces loyalty. Furthermore, consumer satisfaction mediates the effects of service quality and consumer trust on loyalty, but does not mediate the effect of product quality. The results highlight the central role of service quality, trust, and satisfaction in building loyalty, and suggest that Mills Sport should prioritise relational and experiential aspects over product attributes alone.